Linguistic Analysis of How Hotel is Named in Berastagi: A Semantic Analysis - Lubis, Juwita Pobian; Yusuf, Muhammad; Putri, Dian Marisha (Talenta Publisher, 2023)
This research aims to analyze hotel names and provide valuable information on semantics analysis regarding of hotel names in Berastagi. The method of this research was qualitative content analysis, which aimed of the research was to describe the lexical meaning compared with toponymy, the pattern and name classifications of hotels in Berastagi. The data collection was done by observation, interview, and documentation. Based on the result of the study, the findings revealed that the lexical meaning found varied related to the Cambridge Dictionary and KBBI V. The toponymy meaning of hotel names is also various associated with the cultural values of the people in Berastagi Sub-district. Some hotel names use Bahasa Indonesia, Karo, English and some are mixed. The dominant hotel names use Indonesian noun phrases with noun + noun patterns. There are six names classification used, i.e (1) Naming Based on Place, (2) Naming Based on Distinctive Characteristics, (3) Naming Based on Mention Apelativa, (4) Naming Based on Inventor Hope, (5) Naming Based on Mention of Parts (Sinecdoche), (6) Shortening(Abbreviation).